2007
DOI: 10.1016/j.ejheart.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular cardiomyoplasty in large myocardial infarction: Can the beneficial effect be enhanced by ACE‐inhibitor therapy?

Abstract: Background: Cellular cardiomyoplasty with bone marrow derived stromal (MSC) and mononuclear (BMNC) cells has been shown to improve performance of infarcted hearts. We performed a comparative study with MSC and BMNC and tested the hypothesis that captopril treatment could enhance the beneficial effect of cell therapy in large myocardial infarctions. Methods: Male syngeneic Wistar rats underwent experimental infarction and were randomized to receive 1-3 × 10 6 MSC, 10 8 BMNC or vehicle (BSS group). Two additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
17
2
Order By: Relevance
“…We demonstrated that bone marrow stromal cells alone ameliorate cardiac performance in healed infarcted rat hearts [1] and bone marrow monuclear cells when associated with classical pharmacological approaches as angiotensin converting enzyme inhibitors restored the functional competence of rat hearts with large infarcts [2]. However, intracardiac cell injection constitutes an invasive surgical intervention.…”
Section: Introductionmentioning
confidence: 96%
“…We demonstrated that bone marrow stromal cells alone ameliorate cardiac performance in healed infarcted rat hearts [1] and bone marrow monuclear cells when associated with classical pharmacological approaches as angiotensin converting enzyme inhibitors restored the functional competence of rat hearts with large infarcts [2]. However, intracardiac cell injection constitutes an invasive surgical intervention.…”
Section: Introductionmentioning
confidence: 96%
“…Another potential mechanism to explain serum T3 normalization lies in D3 activity. If high cardiac D3 activity is associated with low serum thyroid hormones in the early phase of HF (38), T3 normalization observed in the late phase could be secondary to D3 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular (LV) MI was induced following the procedure described by Johns and Olson 18 and modified in our laboratory 1,5,6 . Briefly, male Wistar rats (200–250 g) were anaesthetized with ketamine (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…These beneficial effects are also evident on electrocardiographic examination 5 . In addition, using the same experimental model, we demonstrated that the beneficial effects of stem cell therapy could be enhanced by ACEI pretreatment, probably due to decreases in infarct size that ultimately improve diastolic function 6 …”
Section: Introductionmentioning
confidence: 99%